Sex Differences in Stress and Group Housing Effects on the Number of Newly Proliferated Cells and Neuroblasts in Middle-Aged Dentate Gyrus - Tzeng, Wen-Yu; Wu, Hsin-Hua; Wang, Ching-Yi; Chen, Jin-Chung; Yu, Lung; Cherng, Chianfang G. (Frontiers in Behavioral Neuroscience, 2017)
Sex differences in stress and coping responses have been frequently documented in aged people, while whether such differences in aged people may appear at the middle age are unknown. This study was undertaken to study the impact of acute stress and social interaction on early neurogenesis in the dentate gyrus (DG) and hippocampus-related memory in two sexes of middle-aged mice. The number of newly proliferated cells, neuroblasts in DG, the object recognition and location memory in 9-month-old male and female C57BL/6N mice were assessed under baseline conditions as well as following an acute stressor regimen and group housing. Three conspecific companions, serving as “the housing group”, were used to model the social interaction throughout the stressor regimen. Males had lower numbers of newly proliferated cells and neuroblasts under baseline conditions as compared to females. The stressor regimen caused rapid decreases in the number of newly proliferated cells and neuroblasts in female DG but no obvious changes were observed in male DG. Group housing, regardless of companions’ age, prevented the stress-induced decreases in the number of newly proliferated cells and neuroblasts in female DG. In contrast, the presence of young or age-matched companions potentiated the stress effect in males by decreasing the number of newly proliferated cells and neuroblasts. Finally, neither the stressor regimen nor group housing affected mouse performances in the object recognition and location memory in either sex. These findings, taken together, provide evidence to support a notion that middle-aged females appear to demonstrate more stress susceptibility on early neurogenesis in DG as compared to middle-aged males, although the hippocampus-related memory performances are comparable and not affected by stress in these males and females. Experiencing stress, middle-aged females are more prone to benefit from social interaction as compared to middle-aged males in this regard. We suggest, accordingly, that involving social interaction may afford a therapeutic advance in preventing stress-produced decreases in early neurogenesis in middle-aged females’ DG.